2003
DOI: 10.1530/eje.0.1480597
|View full text |Cite
|
Sign up to set email alerts
|

Influence of renal function on clinico-pathological features of primary hyperparathyroidism

Abstract: Objective: Disturbed renal function may play an important role in the clinico-pathological presentation of primary hyperparathyroidism (pHPT). We studied the influence of renal function on the clinicopathological characteristics of 141 patients (123 women and 18 men) with surgically proven pHPT. Methods: The 141 patients were assigned to one of two groups based on creatinine clearance (C cr ) level: a renal insufficiency group (n ¼ 37) in which C cr of patients was ,70 ml/min and a normal renal function group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 25 publications
(25 reference statements)
0
24
0
8
Order By: Relevance
“…Therefore, with dietary phosphorus excess, PTH increases and 1,25(OH) 2 D decreases, whereas the opposite occurs with dietary phosphate depletion (23). We recently reported that clinico-pathologic features of pHPT were notably influenced by even moderate renal insufficiency (24). We observed a higher phosphate excretion rate but lower 24-h urinary phosphate excretion in patients with pHPT and renal insufficiency (Ccr of , 70 ml/min) than in patients with normal renal function (25).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, with dietary phosphorus excess, PTH increases and 1,25(OH) 2 D decreases, whereas the opposite occurs with dietary phosphate depletion (23). We recently reported that clinico-pathologic features of pHPT were notably influenced by even moderate renal insufficiency (24). We observed a higher phosphate excretion rate but lower 24-h urinary phosphate excretion in patients with pHPT and renal insufficiency (Ccr of , 70 ml/min) than in patients with normal renal function (25).…”
Section: Resultsmentioning
confidence: 99%
“…В 13-15% случаев выявляются одиночные камни, в 25-30% -множественные и в 30-32% случаев -конкременты в обеих почках. Конкре-менты в почках при ПГПТ состоят преимуществен-но из оксалатов или фосфатов кальция [54,55].…”
Section: сцинтиграфию с 99munclassified
“…Почечная недо-статочность является одним из наиболее тяжелых и малообратимых осложнений и связана с более вы-раженными клиническими проявлениями, повы-шением риска смерти, увеличением распространен-ности артериальной гипертензии [2,9,55]. Cниже-ние СКФ до ХБП 3-й стадии диагностируется у 17-20% с ПГПТ, при этом часть пациентов могут иметь мягкую форму заболевания [56].…”
Section: сцинтиграфию с 99munclassified
“…The impact of renal function on the biochemical expression of PHPT has been well documented (45,46,47,48,49). Several studies clearly identify a correlation between PTH levels and degree of renal impairment in PHPT (50), but the eGFR threshold in PHPT, below which a significant stimulus elevates PTH levels, has not been established.…”
Section: Kidney Function In Phpt Patientsmentioning
confidence: 99%